The response of Melon to Grafting on several cucurbits rootstocks and spraying with aqueous extract of some animals organic fertilizers in the plant growth - Hammad, Hameed Salih; Najem, Saja Ahmad (Journal of agricultural, environmental and veterinary sciences, 2020)
A field experiment was carried out at the Horticulture experiment station in the college of Agriculture - University of Diyala – Iraq during spring season 2019, to study the effect of the grafting using different Squash rootstocks and spraying with water extracts of animals organic fertilizers (sheep’s, poultry wastes) on the plant growth. The experiment consisted of two factors: 1- five rootstocks, namely Pumpkin (Cucurbita moschata), ES101F1 (C. Maxima x C.moscchata), Bottle gourd (Lagenaria siceraria), Squash (Cucurbita Pepo) in addition to non - grafted) as a control, 2- spraying with water extracts of organic fertilizers (sheep’s, poultry wastes) in addition to spraying with water only as control. Data were recorded on plant length, number of branches/ plants, leaves number/ plant, leaves area/ plant, leaves content of total chlorophyll, dry mater percentage/ plant and length of main root. The results are listed below: - 1- Melon plants that were grafted on all rootstocks were superiority compared with non- grafted in all above characteristics. 2- Melon plants which grafted on ES101F1 rootstock recorded the highest values in the number of branches, leaves area. The plants which grafted on Pumpkin rootstocks recorded the highest values in chlorophyll content in leaves, main root length. also, bottle gourd rootstock recorded the highest values in, plant length, leaves number/ plant and plant dry mater percentage. 3- The spraying of sheep waste extract was superiority compared with control (spray with water) in most studied character sticks. 4- A significant effect` was detected for interaction between grafting and spraying in all studied character stick the highest values were defected in grafting on ES101F1, Pumpkin Rootstock and sprayed with sheep waste extract.